Analysis of financial risk and health risk for high-cost diseases in an EPS of the city of Bucaramanga, 2018 (GEON Journal (Management, Organizations and Business), 2019)
Introduction: High cost diseases have become today a determinant and indicator of durability, quality and provision of health services in the health promoters (Eps) of the city of Bucaramanga. Added to this, the high cost has been growing in this city in an uncontrolled way, because people are not following conditions of healthy living habits and efficient health controls, which are recommended according to their health scheme, clinical picture and health factors. health identified. All this negatively affects the provision of health services, since it causes a higher administrative cost that entails the protection and provision with quality of health schemes to combat the mitigation of factors and the same high-cost illness. Objective: to analyze the financial and health risk of high cost diseases in an eps of the city of Bucaramanga in 2018. Methodology: a descriptive, cross-sectional, prospective study with a quantitative approach. Conclusions High cost diseases place the eps of the city of Bucaramanga at financial and administrative risk due to the high cost that must be had to mitigate them and improve the quality of life of users.
Keywords: High Cost Diseases; Financial Risk; Health Risk; Health Promotion Company; Quality in health; Health Services